Confesiones y consejos de tres mujeres: how Chicana/Latinas navigate, negotiate, and resist hegemonic structures within higher education - Carmona, Josefina, author; Poon, OiYan, advisor; Gonzales, Leslie, committee member; Muñoz, Susana, committee member; Sagás, Ernesto, committee member (Colorado State University. Libraries, 2020)
The purpose of this qualitative study was to better understand the experiences of Chicana Latinas interested in the professoriate. Rooted in a Chicana Feminist Epistemology, the study utilized a testimomio/platica approach to answer how Chicana/Latinas navigate, negotiate, and resist the hegemonic academic structures that exist in higher education as they traverse the pathway to and through the professoriate. The principal themes emerging from the pláticas highlighted that platicadoras are in a constant state of negotiation, even the slightest deviations for the approved/legitimate standards set forth by academia are considered forms of resistance, and platicadoras live in a constant state of hypervigilance. Utilizing Anzaldúa's (2015) seven steps of conocimiento, the study provides a framework for how to understand the pain and trauma experienced by Chicana/Latina's in their journeys. Resulting from this study is, Un modelo de conocimiento, which provides an opportunity to better understand the nuances of navigation, negotiation, and resistance and how they interact with the stages of conocimiento, building bridges for healing. In collecting, documenting, and sharing roadmaps, Chicana/Latinas reclaim their spaces in the arena of knowledge creation. More importantly, to reimagine the academy, guided by an ethic of love and care, an opportunity to apply Rendon's (2000) Academics of the Heart as well as follow the consejos of the platicadoras.
Confessions and tips of three women: how Chicana/Latinas navigate, negotiate, and resist hegemonic structures within higher education
Keywords: higher education; plática; testimonio; navigation; Chicana/Latinas; professoriate